The Effect Of Environmental Management Accounting And Business Strategy On Environmental Performance - Carissa, Davina Salsabilla In'am; Andayani, Wuryan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Along with increasing environmental challenges and demands for corporate sustainability, industries in the manufacturing sector face pressure to implement environmentally responsible practices. The purpose of this study is to analyze the effect of environmental management accounting and business strategy on environmental performance in manufacturing companies, with green innovation as a moderating variable. This research method uses ordinal logistic regression analysis. The research sample is 32 manufacturing companies in the primary consumer goods sector listed on the Indonesia Stock Exchange during the period 2020-2023. The results showed that companies that implement environmental management accounting well tend to have better environmental performance. In addition, companies with high business strategies tend to have better environmental performance. However, if green innovation is applied simultaneously with environmental management accounting and business strategy, it will reduce environmental performance. This is because, there is a decoupling to gain legitimacy from society. Although companies may adopt environmental standards and green innovations but if not implemented effectively, this may result in limited impact on the company's environmental performance.